Study Of Carbonaceous And Nitrogenous Pollutants In Leachate Of A Sanitary Landfill Site - Lee, A.; Nikraz, Hamid; Hung, Y. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
The characteristics of leachate from a mature landfill site were investigated over a period of six years to provide useful information for the design and management of landfill leachate. Data analysis revealed that low carbonaceous and nitrogenous pollutants can be achieved with proper groundwater and surface water management and also recirculation of leachate to control stabilization of decomposition in the waste layers.